Cascade units for neon isotopes production by rectification method - Bondarenko, V.L.; Simonenko, Yu.M.; Diachenko, O.V.; Matveyev, E.V. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2013)
Basics of neon separation into isotopes by distillation method at T = 28 K are discussed. The required numbers of transfer units of the top and bottom column sections at different loads are calculated. The experimentalcharacteristics of packed rectification columns are presented and examples of the cascade outlined. A scheme ofcryogenic circuit based on the high-pressure throttle neon cycle with intermediate nitrogen cooling is presented. The necessity and the technical ability to create the driving difference of pressures between columns of various stages demonstrated.